Secondary lymphangioma of vulva: A report of two cases - Pushpa Gnanaraj; V Revathy; V Venugopal; D Tamilchelvan; V Rajagopalan (Wolters Kluwer Medknow Publications, 2012)
Secondary lymphangiomas or acquired lymphangiomas of vulva represent dilatation of upper dermal lymphatics following damage to previously normal deep lymphatics. They have been reported to occur following various infections, surgeries and radiotherapy which can cause damage to deep lymphatics.Treatment options in the management of secondary lymphangiomas include surgical resection, carbon dioxide laser vaporisation, sclerosing agents etc. We report two cases of secondary lymphangioma of vulva that followed radiotherapy for carcinoma of cervix. Both the patients were treated successfully by surgery.